2003
DOI: 10.1002/adsc.200390025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Applications of HexaPHEMP, a Novel Biaryl Diphosphine Ligand

Abstract: The novel biaryldiphosphine ligand 1 (HexaPHEMP) has been prepared in five steps from commercially available 3,4,5‐trimethylphenol using a concise synthetic route. This approach also allows fine tuning of the ligand's stereoelectronic properties through the variation of the aromatic groups on the ligating phosphorus atoms. In certain asymmetric hydrogenation processes, catalysts containing this ligand were found to have enhanced activity and selectivity over other biaryldiphosphine‐containing catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(23 citation statements)
references
References 24 publications
1
21
1
Order By: Relevance
“…The preliminary results demonstrate that opposite results were obtained in different bases [KOH or (CH 3 ) 3 COK] when complexes 9a and 9c were used as catalysts (Table 1, Entries 1,2 vs. 4,5). In the solution of (CH 3 ) 3 COK higher enantioselectivity was achieved than in the solution of KOH when 9c was used as catalyst ( 16 Ru(S-MeO-P-Phos)(S,S-DPEN)Cl 2 afforded almost the same ee value as Ru(S-P-Phos)(S,S-DPEN)Cl 2 , but higher enantioselectivity was obtained with Ru(S-MeO-P-Phos)(S-DAIPEN)Cl 2 , Chiral diamine played a more significant role than chiral diphosphine in the asymmetric hydrogenation of acetophenone.…”
Section: Asymmetric Hydrogenation Of Acetophenone Catalyzed By a Sericontrasting
confidence: 48%
“…The preliminary results demonstrate that opposite results were obtained in different bases [KOH or (CH 3 ) 3 COK] when complexes 9a and 9c were used as catalysts (Table 1, Entries 1,2 vs. 4,5). In the solution of (CH 3 ) 3 COK higher enantioselectivity was achieved than in the solution of KOH when 9c was used as catalyst ( 16 Ru(S-MeO-P-Phos)(S,S-DPEN)Cl 2 afforded almost the same ee value as Ru(S-P-Phos)(S,S-DPEN)Cl 2 , but higher enantioselectivity was obtained with Ru(S-MeO-P-Phos)(S-DAIPEN)Cl 2 , Chiral diamine played a more significant role than chiral diphosphine in the asymmetric hydrogenation of acetophenone.…”
Section: Asymmetric Hydrogenation Of Acetophenone Catalyzed By a Sericontrasting
confidence: 48%
“…The use of THF slightly increased the enantioselectivity to 73% yet the reaction was slower (entry 5). Finally, the best results were obtained in dichloromethane with ees up to 96% (entries [6][7][8]. It is clear that the presence of piperidine hydrochloride affects the enantioselectivity of this reaction in dichloromethane (entries 6 and 7).…”
mentioning
confidence: 87%
“…[7] In 2003 Henschke et al reported the use of a diverse library of ruthenium Noyori-type precatalysts (RuPPNNCl 2 ) in the enantioselective hydrogenation of imines. [8] The highest enantioselectivity in the hydrogenation of 2-methylquinoxaline (73% ee) was obtained using (S)-Xyl-HexaPHEMP as ligand with the addition of (S,S)-cyclohexanediamine and potassium tert-butoxide as base. The use of a tethered BIPHEP-type ligand in combinatioin with [Ir-A C H T U N G T R E N N U N G (COD)Cl] 2 and I 2 was reported by Chan, who achieved up to 80% ee in the asymmetric hydrogenation of 1a.…”
mentioning
confidence: 99%
“…In 2003, Henschke group reported asymmetric hydrogenation of 2-methylquinoxaline by using Noyori's catalytic system RuCl 2 (diphosphine)(diamine) with moderate enantioselectivity [98,99]. Chan group reported the hydrogenation of 2-methylquinoxaline using the Ir-PQ-Phos complex as catalyst with up to 80% ee in the presence of iodine [67].…”
Section: Asymmetric Hydrogenation Of Quinoxalinesmentioning
confidence: 99%